2D α-In2Se3 flakes for high frequency tunable and switchable film bulk acoustic wave resonators - Sun, Jiayi (2025)
Tunable and switchable film bulk acoustic resonators (FBARs) with the capability of dynamically adjusting their resonant frequencies hold significant promise for advanced multi-band radio frequency (RF) communication systems. However, tunable and switchable FBARs based on conventional thin ferroelectric materials face several challenges in meeting the demands of advanced RF applications. Specifically, submicron-thick ferroelectric materials suffer from degradation in piezoelectric performance due to the strong scattering of acoustic waves caused by surface defects, as well as the inconsistency in crystal orientation. Recent advances in 2D ferroelectric materials create new opportunities for high-performance tunable and switchable FBARs. Here, the first batch of FBAR chips based on 2D α-In2Se3 flakes is reported. The α-In2Se3-based FBARs are normally under the on-state and possess a small off-voltage of −4 V. A tuning range of 26 MHz is achieved with a control voltage from −2 to 4 V at the resonant frequency of 8.6 GHz. To the best of the author's knowledge, this is the first batch of tunable FBARs that can function beyond the sub-6 GHz band. This work demonstrates for the first time that 2D ferroelectric materials are very promising for high-frequency tunable and switchable FBARs.